Assembling your nanowire: an overview of composition tuning in ternary III–V nanowires. (24th November 2020) - Ghasemi, Masoomeh; Leshchenko, Egor D; Johansson, Jonas
Abstract: The ability to grow defect-free nanowires in lattice-mismatched material systems and to design their properties has made them ideal candidates for applications in fields as diverse as nanophotonics, nanoelectronics and medicine. After studying nanostructures consisting of elemental and binary compound semiconductors, scientists turned their attention to more complex systems—ternary nanowires. Composition control is key in these nanostructures since it enables bandgap engineering. The use of different combinations of compounds and different growth methods has resulted in numerous investigations. The aim of this review is to present a survey of the material systems studied to date, and to give a brief overview of the issues tackled and the progress achieved in nanowire composition tuning. We focus on ternary III x III1− x V nanowires (AlGaAs, AlGaP, AlInP, InGaAs, GaInP and InGaSb) and IIIV x V1− x nanowires (InAsP, InAsSb, InPSb, GaAsP, GaAsSb and GaSbP).